2003
DOI: 10.1099/ijs.0.02647-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and physiological characterization of a heterotrophic, chemolithoautotrophic Thiothrix strain isolated from activated sludge

Abstract: The sheathed filamentous bacterium known as strain CT3, isolated by micromanipulation from an activated sludge treatment plant in Italy, is a member of the genus Thiothrix in the c-Proteobacteria according to 16S rDNA sequence analysis. The closest phylogenetic neighbours of strain CT3 are strains I and Q T , which were also isolated from activated sludge and belong to the species Thiothrix fructosivorans. These strains have respectively 99?2 and 99?4 % similarity to CT3 by 16S rDNA sequence comparison. CT3 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Recently, specific thiosulfate oxidation rates of pure cultures of Thiothrix isolated from activated sludge (32) and Thiothrixdominated activated sludge (24) have been determined to be 1.9 ϫ 10 Ϫ11 and 0.9 ϫ 10 Ϫ11 mmol S 2 O 3 2Ϫ cell Ϫ1 h Ϫ1 , respectively. By multiplying these oxidation rates by the population density of Thiothrix determined in the biofilms (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, specific thiosulfate oxidation rates of pure cultures of Thiothrix isolated from activated sludge (32) and Thiothrixdominated activated sludge (24) have been determined to be 1.9 ϫ 10 Ϫ11 and 0.9 ϫ 10 Ϫ11 mmol S 2 O 3 2Ϫ cell Ϫ1 h Ϫ1 , respectively. By multiplying these oxidation rates by the population density of Thiothrix determined in the biofilms (ca.…”
Section: Discussionmentioning
confidence: 99%
“…7B), like Thiothrix sp. strain CT3 cells (32), and thus were distinguishable from type 021N Thiothrix species (lacking a sheath). In situ hybridization with the SO07-specific probe revealed that a number of rod-shaped SO07 cells (approximately 10 8 cells cm Ϫ3 ) were mainly present along with some filamentous bacteria at the surface (100 m) of the biofilm (Fig.…”
Section: Vol 71 2005 Development Of Internal S Cycle and Sob Populamentioning
confidence: 94%
“…appeared first probably because Thiothrix spp. have an ability to grow heterotrophically or chemolithotrophically with H 2 S and S 2 O 3 2Ϫ as electron donors at a neutral pH (38). Next, Thiomonas spp.…”
Section: Succession Of Concrete Corrosion and Microbial Communitymentioning
confidence: 99%
“…Thiothrix sp. CT3 was isolated from an activated sludge treatment plant in Italy by Rossetti et al (2003). These authors showed that there are several differences between Thiothrix sp.…”
Section: Strains G1mentioning
confidence: 99%